Derajat Integrasi Ekonomi Indonesia Dengan Malaysia Pada Komoditi Kopi - Fitri, Melani Anisa; Syahni, Rahmat; Hendri, Muhammad (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Economic integration aims to facilitate the flow of goods and services between integrated countries by reducing trade barriers, both tariff and non-tariff. At the ASEAN level, implementing economic integration is performed by establishing AFTA. For AFTA's performance to be effective, CEPT and ATIGA schemes are formed. Indonesia and Malaysia have a relationship in AFTA, which is applied one of them in the coffee commodity trade. Because Indonesia is in the position of producers and Malaysia is in the position of consumers. This study aims to analyze the degree of economic integration between Indonesia and Malaysia in coffee from 2001-2020. This study uses the Intra-Industry Index (IIT) approach using the Grubel-Lloyd Index (G-L index) model. Data in this research is secondary data from 2001-2020. The research variables are the volume of Indonesian coffee exports to Malaysia and the volume of Indonesian coffee imports from Malaysia. The results show that Indonesia and Malaysia's average degree of economic integration from 2001-2020 is weak. From 2001-2020 the IIT index fluctuated, with the highest in 2017 at 8.6386 and the lowest in 2011 at 0.169184. From 2001-2020 the most types of coffee exported to Malaysia based on the HS Code were 09011110 (Arabica wib or robusta oib, not roasted, not decaffeinated), while the type of coffee most imported by Indonesia from Malaysia based on the HS Code was 090121200 (Coffee, roasted, not decaffeinated, ground).